2007
DOI: 10.1590/s1519-69842007000500003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the Neotropical otter (Lontra longicaudis Olfers, 1818) in Southern and Southeastern Brazil

Abstract: The Neotropical otter is one of the least known otter species, and it is considered to be threatened to various degrees throughout its geographic range. Little information exists on the ecological characteristics of this species, and no genetic study has been published about it until now, hampering the design of adequate conservation strategies for its populations. To contribute with genetic information to comprehensive conservation efforts on behalf of L. longicaudis, we characterized the molecular diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
4
10
0
2
Order By: Relevance
“…Therefore, calculations were based on a final data set comprising 24 sequences assumed to be from different individuals (see Table 1). This sample size is identical or similar to previous genetic analyses of other Lontra species in South America (Centrón et al 2008;Trinca et al 2007). …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, calculations were based on a final data set comprising 24 sequences assumed to be from different individuals (see Table 1). This sample size is identical or similar to previous genetic analyses of other Lontra species in South America (Centrón et al 2008;Trinca et al 2007). …”
Section: Resultssupporting
confidence: 78%
“…Comparable data for other Lontra species are rare, but a recent study of Southern river otters (Lontra provocax), also classified as Endangered by the IUCN, from two disjunct regions in Argentinean Patagonia yielded only a single mtDNA control region haplotype in 13 individuals, although four different cytochrome b haplotypes were found in 34 animals analysed (Centrón et al 2008). In an analysis of 491 bp of the mtDNA control region the third South-American Lontra species, the Neotropical otter (Lontra longicaudis), was found to exhibit a haplotype diversity similar to ours (0.82), but a more than twofold lower nucleotide diversity of 0.0049 (Trinca et al 2007). Neotropical otters are also considered to be threatened, but, due to lack of information, their present IUCN status is Data Deficient.…”
Section: Resultssupporting
confidence: 58%
“…The number of NGS-based studies taking place on Eurasian otters has increased significantly, and there are also a few recent studies on some of the less well-known otter species (e.g. Garcia et al 2007;Trinca et al 2007;Koepfli et al 2008). There has been, however, no evaluation of existing studies and methods for otters as yet, though such reviews have been found very useful for other species, such as bears (Paetkau 2003;Bellemain et al 2005;Solberg et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Putman (1984), as fezes são um importante meio utilizado pelos mamíferos para a marcação de território. Apesar de não ser possível estimar a população da espécie no Rio das Pombas (controle) sem um método específico para este objetivo, como o uso do DNA presente nas fezes (Trinca et al, 2007(Trinca et al, , 2013, a ocorrência da lontra nesse rio foi confirmada por meio de expressiva quantidade de amostras fecais, evidenciando que este possui características ambientais favoráveis à ocupação pela espécie.…”
Section: Resultsunclassified